Htlv-2 infection in manaus, brazil: First description of htlv-2c subtype in an urban area of the western amazon region - Pontes, Gemilson Soares; Ribeiro, Hygor Halyson Figueiredo; Toro, Diana Mota; Neto, José Pereira De Moura; Souza, Victor C.; de Almeida, Maria Edilene Martins; Nascimento, Valdinete Alves do; Costa, Cristóvão Alves da; Naveca, Felipe Gomes; Santos, Mike Barbosa; Vallinoto, Antônio Carlos Rosário (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Introduction: We investigated the prevalence of human T-cell lymphotropic virus types 1 and 2 (HTLV-1/2) infection in patients with hematological diseases from the western Amazon region of Brazil. Methods: Samples from 306 patients were submitted for the molecular diagnosis of HTLV-1/2 infection by real time PCR (qPCR), with amplification, sequencing, and phylogenetic analysis of the long terminal repeat (LTR) region. Results: A 29-year-old male carrier of sickle cell anemia with a history of multiple blood transfusions was diagnosed with the HTLV-2c subtype. Conclusions: This study describes the first known occurrence of HTLV-2c in the urban area of Brazil’s western Amazon region. © 2020, Sociedade Brasileira de Medicina Tropical. All rights reserved.